Laser shock composite microforming of Fe-based amorphous alloys. (15th March 2021) - Gu, Xin; Wang, Xiao; Cui, Jiankun; Ma, Youjuan; Zhang, Haokun; Wang, Keyang; Lu, Jiaxin
Abstract: To address the shortcomings of Fe-based amorphous alloys that are difficult to plastically form at room temperature, this study used high strain rate laser instead of traditional loading methods to conduct composite microforming of drawing, punching, and blanking. This article mainly explored the influence of laser energy and soft film thickness on the forming accuracy and depth, morphological characteristics, thickness distribution and mechanical properties. Result showed that the forming accuracy increased with the increase in the laser energy. However, the forming depth decreased when the laser energy was large. The forming accuracy was good when the soft film thickness was small. Abundant shear bands were distributed on the surface, indicating that the plastic deformation was realized on the basis of the generation and propagation of the shear bands. The cross-sectional morphology was also composed of smooth and choroid regions, and their composition ratio also varied in different regions. The bottom region had the smallest thickness, and the flange region had the largest thickness. The distribution of the nanohardness on cross-section was roughly the same as that of the workpiece thickness. The nanohardness was small when the thickness was thin. The elastic modulus gradually decreased from the flange region to the bottom region.